The Data Management Transformation in the Capital Market: A Case Study of PT XYZ in the Centralization and Sharing Strategy of Investor Data Through the ABC System - Pungkas Budhi Santoso; Buddi Wibowo (Dinasti Publisher, 2024)
This study is conducted using a robust research methodology. It aims to analyze the capacity and capabilities of PT. XYZ in implementing the strategy of Investor Data Centralization and KYC Data Sharing through the ABC System. This strategy aims to provide centralized KYC storage and KYC data sharing through the ABC (Centralized Investor Data Management System) platform, which participants in the Indonesian capital market sector can utilize. The study employs both external analysis (PESTEL model, Porter's Diamond, and comparative analysis with KYC platforms in other countries) and internal analysis (Value Chain and VRIO Framework) to assess PT XYZ's capacity and capability in executing this strategy. The effectiveness of this strategy is measured through EFE, IFE, IE and SWOT matrices. The research findings are expected to offer strategic insights into opportunities and challenges in KYC data centralization strategies, provide recommendations for optimizing CORES services, and contribute to the strategic management literature in the financial sector, especially in the context of KYC regulation and technology.